PROBLEMS AND PRACTICAL NEEDS IN LEARNING SPEAKING IN HIGHER EDUCATION - Baiq Resti Rizanti; Lalu Thohir; Kurniawan Apgrianto (Wiralodra English Journal, 2024)
This research aimed to find out the student's problems and practical needs in learning speaking. It employed qualitative methods that gathered responses from 40 out of 233 students in the second semester of the English Department at the University of Mataram. The questionnaire and interview were used to collect the data needed. The questionnaire consisted of 20 questions and was distributed using Google Forms, and the interview utilized 5 questions to elicit more detailed responses from the respondents. The collected data were analyzed systematically through the data reduction, display, and conclusion stages. The findings of this research showed that the students not only had linguistic problems, such as lack of pronunciation, grammatical knowledge, and vocabulary mastery, but they also faced psychological problems including fear of making mistakes, shyness of speaking in front of the class, anxiety, and not having enough confidence. Further, to improve their speaking skills, the students required more practice and exercises inside and outside the classroom with suitable speaking materials for their level. Additionally, focusing on activities rather than just materials and providing constructive feedback whenever they make mistakes will be crucial for their learning.